2016
DOI: 10.1038/nphys3715
|View full text |Cite
|
Sign up to set email alerts
|

Coincidence of a high-fluence blazar outburst with a PeV-energy neutrino event

Abstract: The discovery of extraterrestrial very-high-energy neutrinos by the IceCube collaboration has launched a quest for the identification of their astrophysical sources. Gamma-ray blazars have been predicted to yield a cumulative neutrino signal exceeding the atmospheric background above energies of 100 TeV, assuming that both the neutrinos and the γ-ray photons 2 are produced by accelerated protons in relativistic jets. Since the background spectrum falls steeply with increasing energy, the individual events with… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
193
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 235 publications
(202 citation statements)
references
References 45 publications
6
193
0
3
Order By: Relevance
“…Coincidences in time and space of astrophysical neutrino events with exceptional flares of blazars have been proposed by several authors (e.g. [80]). Among the speculated possible origins of the IceCube events are GRBs with jets shocked in surrounding matter.…”
mentioning
confidence: 99%
“…Coincidences in time and space of astrophysical neutrino events with exceptional flares of blazars have been proposed by several authors (e.g. [80]). Among the speculated possible origins of the IceCube events are GRBs with jets shocked in surrounding matter.…”
mentioning
confidence: 99%
“…However, one distinguishing characteristic of hadronic models would be the expected neutrino emission from charged pion or neutron decay resulting from interactions between high energy protons and photons (Mannheim & Biermann 1989). It has been claimed that the bright gamma-ray flare observed in the blazar PKS B1424-418 is hadronic in nature due to the detection of a PeV-energy neutrino with a high degree of positional and temporal coincidence (Kadler et al 2016) by the IceCube neutrino detector. However, the detection rate of IceCube high energy neutrinos is so low that this is not expected to be a very robust means of distinguishing between hadronic and leptonic models for blazars.…”
Section: Alternatives To Ic/cmbmentioning
confidence: 99%
“…It is however likely unrelated given the large implied neutrino luminosity. Padovani et al (2016) observe a correlation between extreme blazars and highenergy neutrino events and Kadler et al (2016) found a bright gamma-ray outburst of a blazar which was aligned with a multi PeV neutrino event. However, all of these associations have a chance-coincidence probability of a few percent and are hence not significant detections.…”
Section: Introductionmentioning
confidence: 99%